The Impact of Product Quality, Price Perception, and Promotion on Consumer Purchase Decision at Esperto - Rikky Alfadilah; Aris Budiono (SEAN Institute, 2025)
This study aims to examine the impact of three key factors product quality, price perception, and promotion on consumer purchasing decisions at Esperto Coffeeshop. The research addresses the critical problem of understanding how these factors influence consumer behavior, particularly in the competitive coffee industry. A quantitative approach was used, with data collected from 150 respondents who have previously purchased products from Esperto. The primary objective of the study is to analyze the relative impact of these three factors on purchase decisions, with a focus on identifying which variable has the most significant influence on consumer choices. The results of the statistical analysis, including multiple regression, F-test, and R-squared calculations, reveal that price perception and promotion have a more substantial effect on consumer purchase decisions than product quality. The regression model explains 41.6% of the variation in purchase decisions, indicating that these three factors collectively influence consumer behavior, but other factors outside the study also contribute to purchase decisions. This study underscores the importance of integrating product quality, competitive pricing, and effective promotional strategies to enhance consumer decision-making at Esperto Coffeeshop. Based on these findings, it is recommended that Esperto develops a marketing strategy that optimally combines these three factors to strengthen its market position and attract more customers.